Environmental impacts of earthquake hazards: Indian scenario - Dev, Pramendra (Journal of Nepal Geological Society, 1998)
An overview of environmental consequences resulting due to earthquake phenomena in various parts of India, is presented. The prominent characteristics of major earthquake operations as well as the damages caused to environmental regime and human population are enumerated. The problems of earthquake prediction and control are also discussed. Prediction of hazardous earthquake activity can be made on the different criteria such as: seismicity pattern preceding large earthquake, recurrence intervals of earthquake events, dilatancy phenomena of high strain zone, changes in groundwater levels and composition and anomalous animal behaviour. However, precise technique for short term prediction is still to be evolved. Earthquake disasters can be reduced to some extent by adopting adequate remedial measures before, during and after the activity. It is opined that the environmental awareness should be exercised to educate people regarding the defensive operations to protect themselves from adverse effects of earthquakes. The appropriate steps such as schemes of landuse planning, regulation of structural design, and provisions of earthquake insurance programmes may be considered for implementation on priority.